(untitled) (Al-Qamar, 2024)
Allama Iqbal is a poet of life, creation, evolution, passion and love. Life is a creative process for them. According to Iqbal, the value of this art is that it is life-giving and an interpreter of life. However, according to them, skill and art should be such that it is possible to achieve the highest values ​​of life, to lead the society from low to high. According to Iqbal, art is that which gives life and is the interpreter of life, which moves the dead and depressed emotions, which teaches to live and die for a higher purpose. The true art is the one who makes his art a means of curing national diseases, the purpose of art is to enhance the beauty of life and to lead the society from low to high, to familiarize with the pleasure of revolution and to usher in a new era, a new era. In the search for revolution, one has to keep a hot head. Iqbal Jalali attaches great importance to trend. It is an expression of glory and self-power, creative values, creative meanings and the existence of the universe depends on it.